2014
DOI: 10.1016/j.psychres.2014.04.011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of language on functional capacity assessment in middle-aged and older US Latinos with schizophrenia

Abstract: The U.S. Latino population is steadily increasing, prompting a need for cross-cultural outcome measures in schizophrenia research. This study examined the contribution of language to functional assessment in middle-aged Latino patients with schizophrenia by comparing 29 monolingual Spanish-speakers, 29 Latino English-speakers, and 29 non-Latino English-speakers who were matched on relevant demographic variables and who completed cognitive and functional assessments in their native language. There were no stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…This study focused on the validation process of a translated and culturally adapted measure of Functional Capacity in Schizophrenia, the Brazilian version of the UCSD Performance-based Skills Assessment (UPSA-1-BR). Supported by existent evidences ( Bengoetxea et al, 2014 ) and based on our results, we believe that the adaptation process (language and culture) didn’t interfere with the original instrument’s essence.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This study focused on the validation process of a translated and culturally adapted measure of Functional Capacity in Schizophrenia, the Brazilian version of the UCSD Performance-based Skills Assessment (UPSA-1-BR). Supported by existent evidences ( Bengoetxea et al, 2014 ) and based on our results, we believe that the adaptation process (language and culture) didn’t interfere with the original instrument’s essence.…”
Section: Discussionsupporting
confidence: 82%
“…UPSA and its brief version (UPSA-B) had already been validated in a number of western developed countries ( Heinrichs et al, 2006 , Harvey et al, 2009 , Helldin et al, 2012 , Garcia-Portilla et al, 2013 ) and also had been used to access a specific ethnicity ( Cardenas et al, 2008 , Bengoetxea et al, 2014 ) inside a multicultural country (USA). Recently, a Japanese version of the UPSA-B was validated ( Sumiyoshi et al, 2014 ), the first one in a non-western developed country.…”
Section: Introductionmentioning
confidence: 99%
“…Seven studies presented outcomes that were non-prespecified: three articles-corresponding to one study-reported linguistic analysis [25][26][27] and four did not report overall or particular scores for psychiatric symptoms [28][29][30][31]. Three studies presented inappropriate study designs, case reports [15,32,33], and two studies presented wrong interventions focusing on cross-cultural studies [34,35]. Finally, four studies were included in the meta-analysis [16,[36][37][38].…”
Section: Search Resultsmentioning
confidence: 99%
“…Quantitative assessment of the correlation between the UPSA and the GAF was based on 11 pairs of estimates from nine studies, which reported the overall UPSA score, or enough information to derive it. Of these, six studies reported the UPSA [37, 40, 42, 43, 47, 60], and three studies reported the UPSA-B [35, 41, 45]. Baseline characteristics of the patient populations in these studies showed that the majority of studies included more males than females; two studies had samples with an average age < 30 years, while the rest of the studies had a mean age of ≥ 40 years.…”
Section: Resultsmentioning
confidence: 99%